2017
DOI: 10.1111/dom.13169
|View full text |Cite
|
Sign up to set email alerts
|

Practical strategies for improving outcomes in T2DM: The potential role of pioglitazone and DPP4 inhibitors

Abstract: T2DM is a complex disease underlined by multiple pathogenic defects responsible for the development and progression of hyperglycaemia. Each of these factors can now be tackled in a more targeted manner thanks to glucose‐lowering drugs that have been made available in the past 2 to 3 decades. Recognition of the multiplicity of the mechanisms underlying hyperglycaemia calls for treatments that address more than 1 of these mechanisms, with more emphasis placed on the earlier use of combination therapies. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 114 publications
0
15
0
2
Order By: Relevance
“…Emerging therapies using direct GLP-1 and GIP agonists will benefit greatly from a more thorough understanding of extrapancreatic incretin biology. Our results suggest the potential for synergy of TZD and incretin agonist therapy (47).…”
Section: Discussionmentioning
confidence: 65%
“…Emerging therapies using direct GLP-1 and GIP agonists will benefit greatly from a more thorough understanding of extrapancreatic incretin biology. Our results suggest the potential for synergy of TZD and incretin agonist therapy (47).…”
Section: Discussionmentioning
confidence: 65%
“…Vascular lesions induced by DM often cause pathological changes to the tissues and organs (6). Blood vessels transport blood, secreting bioactive substances, regulating blood pressure and maintaining tissue and organ perfusion (7). It has been demonstrated that microvascular lesions cause diabetic ophthalmopathy and nephropathy and that DM-induced vascular injuries are a key factor in the development of microvascular lesions (8).…”
Section: Introductionmentioning
confidence: 99%
“…Other side effects such as edema [21] and bone fractures [22] were also related to the use of pioglitazone. In a previous study, TECOS in adjunct to DMBG prevented weight regain more effectively than DMBG alone in obese women with PCOS previously treated with liraglutide [6].…”
Section: Discussionmentioning
confidence: 99%